PENGARUH GAYA KEPEMIMPINAN PARTISIPATIF, LINGKUNGAN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI PADA BAGIAN KEPERAWATAN RSUD TUGUREJO SEMARANG) - Insan, Pribadi Darmawan; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2016)
Problems that occur in hospitals Tugurejo Semarang is employee performance of nursing less than the maximum. It is shown from the number of complaints from customers who go into the hospital management Tugurejo Semarang where most complaints are directed at the nursing Tugurejo Hospital Semarang. Less than the maximum employee performance is thought to be caused due to several factors namely participative leadership style, work environment, compensation and organizational culture. This study aimed to analyze the influence of participative leadership style, work environment, compensation and organizational culture on employee performance of nursing Tugurejo Hospital Semarang. The population used in this study were employees Tugurejo Hospital Semarang. The sampling technique used was purposive random sampling. Criteria samples taken were employees Tugurejo Semarang Hospital nursing sections totaling 73 nurses. Methods of data collection in this study using questionnaires and interviews. Methods of data analysis using multiple linear regression analysis.Based on this research, work environment, compensation and organizational culture influence on employee performance of nursing Tugurejo Hospital Semarang, whereas participative leadership style has no effect on employee performance of nursing Tugurejo Hospital Semarang. Employee performance is able to be explained by the independent variable is the participative leadership style, work environment, compensation, and organizational culture at 86.5%.